Ibn al-ʾArab on the three conditions of Tawba - Khalil, Atif (Islam and Christian-Muslim relations, 2006)
Although generally translated as ‘repentance’, tawba, like its Hebrew equivalent, teshuvah, simply means ‘turn’ or ‘return’. It is used in the Qur'an to describe actions of both human beings and God. Even though the idea of tawba subsumes the notion of ‘repentance’ (from the Latin paenitere, ‘to be sorry’, ‘to grieve’, or ‘to regret’), its meaning is not limited to that. The tendency within much of Western scholarship on Islam to understand tawba simply as repentance, and mostly human repentance, may well reflect certain presumptions about repentance and its place in religious life, which, one might argue, are absent in Islam. This article explores the understanding of tawba in the thought of Ibn al-ʾArab (1165–1240 CE), whose most extensive reflections on it appear in chapters 74 and 75 of his Meccan Revelations. It focuses on the first of these chapters which concentrates primarily on the conditions set by many of the religious authorities as the fundamental components of human tawba. Ibn al-ʾArab's response reflects certain central motifs that permeate his literary oeuvre. These motifs and their wider relation to his views on tawba will be highlighted as our discussion of this important Sufi maqām (station) unfolds.